INCREASING STUDENTS’ READING SKILL BY USING WATTPAD APPLICATION IN EIGHTH-GRADE STUDENTS OF SMPN 3 WATAMPONE - Almira Adnan; Restu Januarty Hamid; Nurfaizah Sahib (Teaching English as a Foreign Language Overseas Journal, 2023)
This research aims to know the impacts of using Wattpad Application in order to increase students’ reading skill in Eighth-grade at SMPN 3 Watampone. And this research focused on pre-experimental method with one group in pre-test and post-test. The treatment was conducted after the pre-test and before post-test. The population in this research were students of Eight-Grade at SMPN 3 Watampone in 2022/2023 academic year. The writer took 176 students as the population with random sampling technique was used to take one class as the research sample, totaling 23 students. Data obtained from reading test in form of multiple-chooses. The results of this study revealed that there is increasing students reading skill using Wattpad Application based on students’ scores between the pre-test and post-test. The mean score of the students’ reading skill increase from 54,34 in the pre-test to 78,47 in the post-test. Meanwhile the analysis of students’ increasing score from both test (pre-test, post-test) was 30%. So, based on that analysis, it can be concluded that the using Wattpad Application can greatly increase students’ reading skill.